La Soumaâ du Khroub ou l’invention du « Tombeau de Massinissa » - Mathilde Cazeaux (L’Année du Maghreb)
Near Constantine (Algeria) lies a Numidian tomb. It is usually called Soumaâ du Khroub (“Tower of El Khroub”) or “Tomb of Massinissa”, alluding to a famous king of Numidia (202-148 aC). The present article examines the steps of the patrimonalization of this building, and how associating it with the memory of a historical figure contributes to this process. The Soumaâ has been listed, described and assumed as a heritage site since the conquest of Algeria and the scientific expeditions in the wake of it. In the early 20th century, French academics attributed the tomb to Massinissa. After the independence of Algeria, new analysis proved this hypothesis wrong, but Algerian institutions and media still name it this way. The memory of the Numidian king mainly brings coherence to the current site, whose degree of patrimonalization the last part of this article aims to estimate.